A Halpern Type Iterative Scheme for a Finite Number of Mappings in Complete Geodesic Spaces with Curvature Bounded above. (26th October 2021) - Kimura, Yasunori; Sasaki, Kazuya
Abstract: In this paper, we show a convergence theorem to a common fixed point for finitely many mappings by the Halpern's iterative scheme using balanced mappings on an admissible complete CAT(1) space.